WEB PROFIL PERUSAHAAN PT. PERKEBUNAN NUSANTARA VI JAMBI - Lisdarti - (JURNAL AKADEMIKA)
This Scholary report explain about processing Company Profile using web basis and processing data report from branch office to main office PT. Perkebunan Nusantara VI Jambi to simply in processing data report along with other company data, ease official employee to reporting agricultural produce from branch office, save time and conserve energy. This Web production made by intype editor and Personal Home Page (PHP) language. interface use Cascading Code Sistem (CSS). Data or information which related with this research receive by field research and literature research. Conclusion which writer found in making this web is extend information to public become simply, along with report form working so good and efisien because save time and conserve energy